Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1994
DOI: 10.1007/bf00212985
|View full text |Cite
|
Sign up to set email alerts
|

Controlled trial of high-versus low-dose aspirin treatment after percutaneous transluminal angioplasty in patients with peripheral vascular disease

Abstract: Percutaneous transluminal angioplasty of aortoiliac and femoropopliteal atherosclerotic lesions can provide long-lasting hemodynamic improvement. High-dose aspirin is commonly prescribed as reocclusion prophylaxis, but low doses would be preferable because of fewer adverse effects. We performed a double-blind, randomized, controlled clinical trial in patients with peripheral vascular disease with lesions appropriate for angioplasty. We compared the efficacy and side effects of two doses of aspirin (50 mg vs. 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 23 publications
0
15
0
1
Order By: Relevance
“…However, the majority of the data used in this analysis was drawn from trials of low-dose aspirin in cerebrovascular or peripheral vascular disease. Here aspirin doses as low as 30 to 50 mg daily (5,8) have been extensively studied and provide equivalent protection from death, non-fatal stroke, or MI as higher doses. Kong et al (27), using random effects models, have re-examined the Antithrombotic Trialist's data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the majority of the data used in this analysis was drawn from trials of low-dose aspirin in cerebrovascular or peripheral vascular disease. Here aspirin doses as low as 30 to 50 mg daily (5,8) have been extensively studied and provide equivalent protection from death, non-fatal stroke, or MI as higher doses. Kong et al (27), using random effects models, have re-examined the Antithrombotic Trialist's data.…”
Section: Discussionmentioning
confidence: 99%
“…The evidence to support the equivalent efficacy of aspirin doses between 75 and 325 mg is mainly drawn from indirect comparisons between trials of different aspirin dose and direct comparisons in patients with cerebrovascular (5-7) or peripheral vascular (8) disease. There have been only two small direct comparisons of low and intermediate aspirin doses in patients with ACS, only one of which has been published (9).…”
mentioning
confidence: 99%
“…The doses tested ranged from 50 mg / day to 1000 mg / day. The three studies showed that higher doses of aspirin had no advantage on early reocclusion (within one month) and were more likely to cause gastrointestinal side effects including peptic ulcer (Weichert et al, 1994;Minar et al, 1995;Ranke et al, 1994).…”
Section: Aspirin With or Without Dipyridamolementioning
confidence: 99%
“…31 †Includes two trials comparing 75-325 mg aspirin daily v <75 mg aspirin daily 32 33 and one trial of 500-1500 mg aspirin daily v <75 mg aspirin daily. 34 ‡Includes cilostazol, sulotroban, trapidil, E5510, eptifibatide, and GR32191B. Stratified ratio of odds of an event in regimen 1 group to that in regimen 2 group is plotted for each group of trials (black square) along with its 99% confidence interval (horizontal line).…”
Section: Figmentioning
confidence: 99%